2019
DOI: 10.1109/access.2019.2924293
|View full text |Cite
|
Sign up to set email alerts
|

Review Paper on Transmitarray Antennas

Abstract: This paper presents a thorough review of transmitarray devices particularly aiming antenna beamsteering, gathering some of the most relevant solutions published by the scientific community in the field. First, the background for realizing 1-D and 2-D antenna beamsteering with a transmitarray is introduced. Subsequently, several examples of unit-cells for transmitarray implementation and complete transmitarray designs presented in the literature are outlined. Each solution is analyzed in detail, identifying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 66 publications
(128 reference statements)
0
43
0
Order By: Relevance
“…It is positioned 156 mm (F/D=0.81) above the aperture center, and normally illuminates the aperture to produce an x-polarized incident spherical wave. The proper phase distribution on the array aperture for a focused beam pointed in a specific direction can be calculated using (1) and (6). It is quantized into 0°/180° states under the appropriate Δφ, and thus, the states of the PIN diodes of each 1-bit RTA element are determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is positioned 156 mm (F/D=0.81) above the aperture center, and normally illuminates the aperture to produce an x-polarized incident spherical wave. The proper phase distribution on the array aperture for a focused beam pointed in a specific direction can be calculated using (1) and (6). It is quantized into 0°/180° states under the appropriate Δφ, and thus, the states of the PIN diodes of each 1-bit RTA element are determined.…”
Section: Resultsmentioning
confidence: 99%
“…hanks to their simple phase controlling mechanism, reconfigurable reflectarray antennas (RRAs) [1]- [5] and reconfigurable transmitarray antennas (RTAs) [6]- [32] have become an attractive alternative to traditional phased arrays. By integrating solid-state controlling devices, such as PIN diodes, RF MEMS switches, and varactor diodes, in each constituent element, the RRA and RTA elements are able to produce dynamically controlled phase shifts that collimate the radiation from feed and electronically steer the main beam.…”
Section: Introductionmentioning
confidence: 99%
“…Transmitarray unit‐cells with reconfigurable phase values offer the greatest flexibility and allow to electronically switch between different radiation patterns. A detailed overview of different reconfigurable unit‐cell approaches is given in [1, 2 ]. Recent publications have shown though that losses in the tunable or switchable devices like varactor diodes are increasing with frequency and strongly affecting the unit‐cell performances regarding insertion loss [3, 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The feed illuminates the array and each element's transmission coefficient is individually designed to convert an incoming wave into an outgoing focused beam. Unlike reflectarray antennas, the feed of transmitarrays locates opposite to the radiation direction therefore the blockage effect is eliminated …”
Section: Introductionmentioning
confidence: 99%
“…Unlike reflectarray antennas, the feed of transmitarrays locates opposite to the radiation direction therefore the blockage effect is eliminated. 5,6 During the past few decades, considerable research efforts have been made to design transmitarray elements for a transmission phase covering 360 together with a high transmission magnitude, such as employing double square ring element, 7 spiral-dipole element, 8 rectangular ring slot element, 9 double ring slot element, 10 Eshaped element, 11 and circular patch with outer ring element. 12 It is observed that above-mentioned designs feature a multilayer structure, which increases the fabrication complexity as well as the overall thickness and the cost.…”
Section: Introductionmentioning
confidence: 99%